Patterns of Location, Concentration, and Trends in Industrial Employment in Costa Rica’s Greater Metropolitan Area (GAM) - Arias Ramírez, Rafael (2012)
This article presents a temporal and spatial analysis of the location and concentration of industrial employment within Costa Rica’s Greater Metropolitan Area (GAM). To this end, the last five Population and Housing Censuses (1963, 1973, 1984, 2000, and 2011) are used, and a series of tools from spatial statistics, geographic information systems, and urban and regional economics are applied to analyze the dynamics of the labor market associated with industry. The results show that over the past 25 years, there has been a process of relocation of industrial activities within the GAM, as some cantons have lost relative importance in the generation of industrial employment, while others have improved their position in this regard. The applied spatial statistical models reveal strong concentrations of industrial employment in seven cantons of the GAM and clusters in two cantons. The study introduces a novel topic in labor market analysis: the origin-destination matrix of industrial employment, which shows that there is significant worker mobility within the cantons of the GAM, helping to understand the internal dynamics of the industrial sector and employment within that sector.